2019
DOI: 10.1590/fst.34717
|View full text |Cite
|
Sign up to set email alerts
|

Ion specificity in determining physico-chemical properties of drinking water

Abstract: Drinking water plays a key role in regulating the daily salt intake, thus potentially affecting (either in positive or in negative direction) the incidence of diet-related pathologies, including nephrolithiasis. Being regarded as wholesome, bottled water is increasingly preferred to tap water. However, its physico-chemical characterization, as reported on the label, is usually limited to pH and conductivity measurements, along with ion content. Dther parameters, which also are likely to influence the processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In a previous work, we studied the surface tension of the same oligomineral waters considered in the present work, finding the surface tension of OW2 to be slightly but significantly higher than that of OW1 [40]. We interpreted this difference as due to the effect of specific ions on the water structure at the interfaces.…”
Section: Discussionmentioning
confidence: 49%
“…In a previous work, we studied the surface tension of the same oligomineral waters considered in the present work, finding the surface tension of OW2 to be slightly but significantly higher than that of OW1 [40]. We interpreted this difference as due to the effect of specific ions on the water structure at the interfaces.…”
Section: Discussionmentioning
confidence: 49%
“…Since using a scale is a simple way to assess the volume of displaced water from its weight, we assumed that tap water density is 1 g/L. This provides a sufficiently accurate volume measurement (error <0.5%) since: (a) pure water density at 20°C is 0.9982 g/L and its dependence on laboratory temperature varies by only 0.2% between 15 and 25°C ( 24 ), and (b) the densities of mineral or tap water differ from that of pure water by <0.1% ( 25 ). Interestingly, we verified that water weight could be measured with sufficient accuracy (±2 mL) using a conventional low-cost kitchen scale.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Numerous studies have indicated that small SO 4 2− intake can promote metabolic reactions in the body and do not immediately threaten public health. However, a large amount of SO 4 2− not only can be converted to sulde via the "sulfur cycle", affecting water quality, but also massive intake can cause kidney stones, skin allergies, gastrointestinal disorders, and chest pain, among other serious consequences; 5,6 thus, SO 4 2− is used as one of the routine detection indicators for domestic drinking water in China. Currently, colorimetry, capillary electrophoresis (CE), 7 ion selective electrodes (ISE), 8,9 and other techniques are widely used worldwide for the detection of SO 4 2− .…”
Section: Introductionmentioning
confidence: 99%